Aplikasi Baca Buku Platform Digital Yang Dirancang Untuk Memfasilitasi Pengguna Dalam Membaca Berbagai Jenis Buku Elektronik - Khoirinnysa Harahap; Richi Andrianto; Sahroki Fikri Harahap; Sariona Sariona; Tiara Siregar; Qodri Mahendar Siregar (Jurnal Penelitian Teknologi Informasi dan Sains, 2023)
Each individual's interest in reading is different, it requires encouragement from both the individual himself and encouragement from outside. Interest in reading in Indonesia is classified as very low compared to other countries. This is also influenced by technology that is developing rapidly. People in Indonesia, especially teenagers, prefer playing on their smartphones rather than reading books. In developing reading interest, visualization plays an important role to create a strong bond between the reader and the text. The purpose of this research is to develop public interest in reading through the Android-based Book Reading application. The Book Reading application is an application that combines text in various types of books with pictures to make visualizations even more interesting. Baca Buku generally also has branching stories, which have different epilogues in each path. This makes Baca Buku different from other game categories because of the minimal interaction and focus on stories. The platform used is an Android-based smartphone. The Baca Buku application was created with the Ren'Py engine and converted into an APK using the Ren'Py Android Packaging Tool (RAPT). This research was conducted to find out what features in the Baca Buku application can increase public interest in reading, find out how the development of Baca Buku can increase public interest in reading, and find out whether the Baca Buku application can increase public interest in reading. The results of this study are to find out what features in the Baca Buku application can increase reading interest, and how to develop the Baca Buku application which can increase public interest in reading.